2010
DOI: 10.1039/b925555a
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of cucurbit[7]uril and cucurbit[8]uril: an exploratory in vitro and in vivo study

Abstract: Cucurbit[n]urils (CB[n]) are potential stabilizing, solubilizing, activating, and delivering agents for drugs. The toxicity of the macrocyclic host molecules cucurbit[7]uril (CB[7]), the most water-soluble homologue, as well as cucurbit[8]uril (CB[8]) has been evaluated. In vitro studies on cell cultures revealed an IC(50) value of 0.53 +/- 0.02 mM for CB[7], corresponding to around 620 mg of CB[7] per kg of cell material. Live-cell imaging studies performed on cells treated with subtoxic amounts of CB[7] show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
265
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(274 citation statements)
references
References 59 publications
(77 reference statements)
4
265
0
5
Order By: Relevance
“…On the one hand, CB [7]'s safety profile and biocompatibility has been well studied with several in vitro, in vivo and ex vivo models [5][6][7]. For instance, several in vitro studies on cell cultures have shown that CB [7] exhibits very low toxicity at up to 1 mM concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, CB [7]'s safety profile and biocompatibility has been well studied with several in vitro, in vivo and ex vivo models [5][6][7]. For instance, several in vitro studies on cell cultures have shown that CB [7] exhibits very low toxicity at up to 1 mM concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The effects observed for an intravenous single dose i.v. injection with a mouse model demonstrated that CB [7] has a very low acute toxicity at a dose of 250 mg/kg, based on a body weight change of less than 10% within 5 days of the injections [5]. The tissue specific toxicity including neuro-, myo-and cardiotoxicity of CB [7] has been examined with the use of ex vivo electrophysiological models.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the hydrophobic interactions within the cavity, the polar carbonyl groups at the portals are capable of stabilizing host-guest complexes by forming hydrogen bonds and ion-dipole and dipole-dipole interactions with appropriate guests [4,5,10]. Research on the host-guest chemistry of CB[n] has attracted great attention on account of the potential application of these materials in the fields of biomedicine [11,12], photochemistry [13], materials science, and nanotechnology [4,5]. In particular, its higher water solubility (approximately 20 mM) [4,14] and intermediate cavity volume (210 Å 3 ) [15] make CB [7] (Figure 1) an attractive host for complexation of guest molecules used in biology and medicine [5,6,16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has become possible to contrast the inclusion properties and binding strengths of this new class of synthetic host molecules with established macrocyclic receptors, such as cyclodextrins and water-soluble calixarenes. In fact, cucurbiturils are competitive in several respects, such as their low toxicity, [13,14] and far superior in many others, particularly their high chemical stability, large complexation-induced pK a shifts, as well as their tight, selective binding (see articles in this special issue).…”
mentioning
confidence: 99%
“…Moreover, it has become possible to contrast the inclusion properties and binding strengths of this new class of synthetic host molecules with established macrocyclic receptors, such as cyclodextrins and water-soluble calixarenes. In fact, cucurbiturils are competitive in several respects, such as their low toxicity, [13,14] and far superior in many others, particularly their high chemical stability, large complexation-induced pK a shifts, as well as their tight, selective binding (see articles in this special issue).Initial investigations on cucurbit[6]uril focused on its binding preferences and the determination of the binding constants of its host-guest complexes. [15][16][17] These studies have continued to attract attention also for the larger homologues, driven, among other things, by the exceptional kinetics and thermodynamics of binding.…”
mentioning
confidence: 99%